NFAT3-FasL axis synchronously regulates apoptosis and necroptosis in murine cochlear outer hair cells after noise trauma - Wang, Wenlun; Yu, Lisheng; Li, Shichang; Han, Lin; Zheng, Hongwei (Frontiers in Molecular Neuroscience, 2024)
Existing studies have indicated that noise induces apoptosis and necroptosis in cochlear outer hair cells (OHCs). However, the role of the extrinsic cell death pathway, initiated by death ligands in the cochlea, remains unknown. In this study, we hypothesized that noise could induce the NFAT3/FasL axis-mediated extrinsic death pathway in the cochlea. We found that NFAT3/FasL signaling was silent in normal OHCs. Noise exposure induced apoptosis and necroptosis in OHCs with specifically high FasL expression. Multiplex immunofluorescence staining revealed that NFAT3 nuclear translocation and FasL upregulation were colocalized in the apoptotic and necroptotic OHCs following noise trauma. Administration of FK506 or 11R-vivit (an specific NFAT inhibitor) blocked NFAT3 nuclear translocation, inhibited FasL expression, mitigated apoptosis and necroptosis, and protected against noise-induced hearing loss (NIHL). Finally, FasL knockdown by delivering siRNA intratympanically attenuated apoptosis and necroptosis in OHCs and alleviated NIHL, confirming the role of FasL in OHC death. Collectively, our study demonstrates that the NFAT3/FasL axis mediates noise-induced extrinsic death pathway in OHCs, leading to their apoptosis and necroptosis.